Do the SEC's enforcement preferences affect corporate misconduct? - Kedia, Simi; Rajgopal, Shiva (Journal of Accounting and Economics, 2011)
Recent frauds have questioned the efficacy of the SEC's enforcement program. We hypothesize that differences in firms' information sets about SEC enforcement and constraints facing the SEC affect firms' proclivity to adopt aggressive accounting practices. We find that firms located closer to the SEC and in areas with greater past SEC enforcement activity, both proxies for firms' information about SEC enforcement, are less likely to restate their financial statements. Consistent with the resource-constrained SEC view, the SEC is more likely to investigate firms located closer to its offices. Our results suggest that regulation is most effective when it is local.